2020
DOI: 10.1038/s41598-020-62127-3
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation ambiguity in the Fibrillin-1 (FBN1) CpG island shore possibly involved in Marfan syndrome

Abstract: Fibrillin-1 (FBN1) is responsible for haploinsufficient and autosomal dominant Marfan syndrome. Even in the same Marfan pedigree, penetrance and expressivity in heterozygous individuals can differ and result in variable disease onset and severity. Thus, other factors in addition to mutations in FBN1 are likely to contribute to the disease. In this study, we examined the regulation of FBN1 in porcine Marfan syndrome model, focusing on DNA methylation patterns distinguishable as wild-type (WT) and FBN1 null (KO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The encoded LTBP2 protein shows strong structural homology with FBN1. Interestingly, the inheritance patterns of EL caused by variants in these 2 genes are different, with variants in the same locus of FBN1 in family 1 producing different degrees of disease severity in different individuals, suggesting that disease severity in patients with FBN1 mutation may be related to the penetrance of FBN1 mutation, 45 whereas the recessive LTBP2 mutations might result in a loss of function. The C -terminal region of LTBP2 binds specifically to the N -terminal region of FBN1 and may have a structural role in the organization of the elastic fiber structure of LTBP2.…”
Section: Discussionmentioning
confidence: 99%
“…The encoded LTBP2 protein shows strong structural homology with FBN1. Interestingly, the inheritance patterns of EL caused by variants in these 2 genes are different, with variants in the same locus of FBN1 in family 1 producing different degrees of disease severity in different individuals, suggesting that disease severity in patients with FBN1 mutation may be related to the penetrance of FBN1 mutation, 45 whereas the recessive LTBP2 mutations might result in a loss of function. The C -terminal region of LTBP2 binds specifically to the N -terminal region of FBN1 and may have a structural role in the organization of the elastic fiber structure of LTBP2.…”
Section: Discussionmentioning
confidence: 99%
“…Marfan syndrome, similarly to HHcy, is associated with elastin dysfunction due to mutations in the brillin-1 gene (119). While homocysteinylation can interfere with elastin deposition and interaction of micro bril-elastin binding proteins in elastic ber assembly by brillin-1 (110), methylation appear to play a role in brillin-1 dependent elastin organization via regulation of brillin-1 gene expression (120). Importantly, analysis of genome-wide methylation patterns revealed that 25% of differently methylated positions, which are signi cantly associated with aortic diameters in patients with Marfan syndrome, are implicated in CVD (121).…”
Section: Discussionmentioning
confidence: 99%
“…However, identification and regulation of secondary factors or modifiers of FBN1 expression is a major challenge. We observed fluctuations in the DNA methylation status of the CpG island shore of the FBN1 promoter [ 40 ], which may be exploited to regulate FBN1 expression. Although techniques such as RNA interference [ 41 ] and microRNA [ 42 ] may be employed, rigorous investigation is essential to optimize the manifestation of symptoms in FBN1 mut/+ MFS pig models.…”
Section: Challenges and Prospects In Disease Model Pigs With Haploins...mentioning
confidence: 99%